Результаты исследования усовершенствованной наклонной камеры зерноуборочного комбайна - Тойлыбаев, М.С.; Садыков, Ж.С.; Альпейсов, Ш.А.; Тойлыбаев, Н.С. (Изд-во КарГУ им. Е.А.Букетова, 2012)
Мақалада жайылым өсімдіктер тұқымын жинауда өнімділікті жоғарылату үшін дəн жинайтын машинаның жаңа ұрпақтағы перспективалы көлбеу қондырғысы жетілдірілді жəне игерілді. Бұл қондырғының ұтымды параметрлері дəлелденіп, тəжірибелер өткізуде қажетті жəне жеткілікті тиісті дəлдікпен қойылған есеп шешімдері үшін тəжірибе жоспарлары қолданылды. To improve performance, harvesting seed pasture plants we have developed and refined a promising new generation of camera tilt grain-harvesting machines. To study the optimal parameters improved feeding channel for harvesting seeds of pasture plants, in particular, methods of wheatgrass our experimental design, which consists in choosing the number and the experimental conditions, necessary and sufficient for the task with the required accuracy.
Results of the study advadced to tilt the camera combine harvester